Isolation of promoters of tissue and ripening-specific strawberry genes by TAIL-PCR and bioinformatic characterization of the sequences - Koncz, Tímea; Tisza, Viktória; Balogh, Andrea; Kiss, Erzsébet; Heszky, László (Acta Agraria Debreceniensis, 2007)
Isolation of ripening- and tissue-specific promoters has become a very important subject of the genetic regulation and plant physiology research in recent years. It could be possible to reveal the regulation of gene expression, and it may be a very useful approach in the biotechnology. In our work, we have isolated promoter regions of genes exhibiting ripening- and tissuespecific expression in our previous experiments, and the data were characterized by bioinformatic methods. In the sequence of the ripening-specific Spatula and ACC-oxidase promoters (ACCoxidase is one of the key-enzymes of ethylene biosynthesis, directly related to the process of ripening); we could identify auxin- and ethylene-related cis-regulatory elements. This suggests that there is an interaction between ripening and ethylene-synthesis, in case of non-climacteric strawberry, too. We investigated the promoter regions of three green receptacle-specific genes (putative nitrilaselike protein, Ring transcription factor and an aquaporin protein) and we could identify several regulatory elements, which refer to hormonal regulation. Additionally, we could find several cisacting elements which associated with stress-responsiveness and endospermium-specific expression.